2000
DOI: 10.2466/pms.2000.91.3.771
|View full text |Cite
|
Sign up to set email alerts
|

Human Olfactory Communication of Emotion

Abstract: Nonhuman animals communicate their emotional states through changes in body odor. The study reported here suggests that this may be the same for humans. We collected underarm odors on gauze pads from 25 young women and men on two different occasions. On one occasion the donors were induced to feel happy by viewing an excerpt from a funny movie whereas on the other, separated by a day, they were induced to feel afraid by watching an excerpt from a frightening movie. One week later, 40 women and 37 men were aske… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
107
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(116 citation statements)
references
References 23 publications
6
107
1
1
Order By: Relevance
“…[31] The odour produced in the axillae under the stressful/fearful experimental conditions is different and distinguishable from normally produced axillary odour. [27,28] We suggest that a rapid flux of apocrine secretion onto the skin surface during stressful and frightening situations is responsible for a strong and distinctive axillary odour. In previous studies of the odour of freshly hydrolysed aprocrine secretions we reported, anecdotally, that the odour was stronger, more pungent and sulphurous than the odour collected on pads worn in the axillae for ≥ 8 h/day.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…[31] The odour produced in the axillae under the stressful/fearful experimental conditions is different and distinguishable from normally produced axillary odour. [27,28] We suggest that a rapid flux of apocrine secretion onto the skin surface during stressful and frightening situations is responsible for a strong and distinctive axillary odour. In previous studies of the odour of freshly hydrolysed aprocrine secretions we reported, anecdotally, that the odour was stronger, more pungent and sulphurous than the odour collected on pads worn in the axillae for ≥ 8 h/day.…”
Section: Introductionmentioning
confidence: 88%
“…Work by Chen and Haviland-Jones has demonstrated the ability of underarm odour to be influenced by mood. [27,28] These researchers collected underarm odours from young men and women under two different conditions: when viewing clips of a 'scary' movie or when viewing clips of a 'funny' movie. Volunteers smelled bottles containing odour pads collected from donors.…”
Section: Introductionmentioning
confidence: 99%
“…Sampling length varies highly in previous studies, ranging from 13 min (Chen and Haviland-Jones 2000) up to 7 nights (Hold and Schleidt 1977) (see Table 1 for details). However, studies typically sample odor over either 24 h (e.g., Ferdenzi et al 2009; or two consecutive nights (e.g., Sergeant et al 2007;Thornhill and Gangestad 1999;Wedekind et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…A variety of infectious diseases are marked by characteristic odors including the "stale beer" smell of tuberculosis and the "butcher's shop" odor of Yellow Fever (Shirasu & Touhara, 2011). The aromas of body odor are proposed to correlate with a sweat donor's personality (Sorokowska, 2013), and to indicate moods including happiness and fear (Chen & Haviland-Jones, 2000). In most cases, these odor signals were noticed by human smellers and reported informally long before being systematically investigated for molecular markers.…”
Section: The Production and Perception Of Body Odormentioning
confidence: 99%